2016
DOI: 10.1007/s00264-016-3363-4
|View full text |Cite
|
Sign up to set email alerts
|

Dual mobility cups in revision total hip arthroplasty

Abstract: This study provided evidence of the advantages of dual mobility cups in all revision THA indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 35 publications
4
10
0
1
Order By: Relevance
“…Compared with other rTHA studies in which a DM cup was used, the aseptic loosening rate was similar: 0% at 1.3 years [21], 13.5% at 7 years [22], and 3.9% at 8.5 years [23]. Given the differences in the type of bone defects between studies, it seems that aseptic loosening appears between 7 and 10 years (mean of 9.6 years in our study).…”
Section: Discussionsupporting
confidence: 65%
“…Compared with other rTHA studies in which a DM cup was used, the aseptic loosening rate was similar: 0% at 1.3 years [21], 13.5% at 7 years [22], and 3.9% at 8.5 years [23]. Given the differences in the type of bone defects between studies, it seems that aseptic loosening appears between 7 and 10 years (mean of 9.6 years in our study).…”
Section: Discussionsupporting
confidence: 65%
“…There are many factors able to cause the failure of R-THA: these have been found to be mostly instability and aseptic loosening. It has been reported that the dislocation rate in R-THA is almost 3 times higher than primary THA [4,5].…”
Section: Introductionmentioning
confidence: 95%
“…12 There are numerous studies and systematic reviews evaluating the use of DM components in both primary and revision THA. [13][14][15][16][17] However, these cohorts have generally included all-cause revisions. More recent studies have looked at high-risk revision groups, with promising shortand mid-term results and dislocation rates ranging from 3% to 21%.…”
Section: Introductionmentioning
confidence: 99%